Biosensors: The Roadmap of Graphene‐Based Optical Biochemical Sensors (Adv. Funct. Mater. 19/2017). (16th May 2017) - Shivananju, Bannur Nanjunda; Yu, Wenzhi; Liu, Yan; Zhang, Yupeng; Lin, Bo; Li, Shaojuan; Bao, Qiaoliang
Abstract : Shaojuan Li, Qiaoliang Bao, and co‐workers review graphene optical biochemical sensors in article number1603918 . The true potential of graphene lies in optical sensors, especially for biochemical sensing in the diagnostics and health care sector. The working principle is based on whenever biomolecules come into contact with graphene, the Fermi level will shift either to p ‐type or n ‐type, changing its opto‐electronic properties.